Patient-specific affect-abdominal pain interactions in endometriosis: an experience sampling method (ESM) study. (3rd July 2022) - van Barneveld, E.; de Hertogh, M.; Vork, L.; van Hanegem, N.; van Osch, F. H. M.; Kruimel, J. W.; Bongers, M. Y.; Leue, C.; Lim, A. C.
Abstract: Objectives: Cross-sectional studies show that endometriosis-related pain is associated with affect. Measuring these symptoms in real-time in a longitudinal perspective yields the ability to analyze the temporal relationship between variables. The aim was to evaluate the association between affect and abdominal pain, using the Experience Sampling Method (ESM) as a real-time, randomly repeated assessment. Methods: Thirty-four endometriosis patients and 31 healthy subjects completed up to 10 real-time self-assessments concerning abdominal pain and affective symptoms during seven consecutive days. Results: Endometriosis patients experienced more abdominal pain and negative affective symptoms, and scored lower on positive affect compared to healthy controls. A significant association was found between abdominal pain and both positive and negative affect in endometriosis patients. For healthy controls, less strong or non-significant associations were found. When looking at abdominal pain as a predictor for affect and vice versa, we found that only in endometriosis patients, pain was subsequently accompanied by negative affect, and positive affect may alleviate pain in these patients. Conclusions: This study confirms a concurrent and temporal relationship between affect and abdominal pain in endometriosis patients and supports the use of real-time symptom assessment to interpret potential influencers of abdominal complaints in patients with endometriosis.